Tenrigangkae Village Funding Analysis Kab. Maros in Encouraging Local Infrastructure and Economic Development - Tantri Dwi Astria; Sarmila; Muttiarni; Sephia Nanda Wulansari; Nurmi; Esti Qama; Muh Rifkiadi Nasir (Pustaka Digital Indonesia, 2024)
Village funding plays a crucial role in supporting infrastructure and local economic development at the regional level. Through effective fund allocation, villages can increase access to basic services such as education and health, as well as improve infrastructure that supports residents' daily lives. This study uses a qualitative approach to explain how village funding contributes to encouraging infrastructure development and the local economy. Data were analyzed through content analysis and life history methods to identify emerging themes and patterns. The research results show that the development of village information systems provides significant benefits, including increased access to information, government transparency, efficiency of public services, active community participation, improved quality of life, better management of natural resources, support for local economic growth, as well as increased security and welfare of society as a whole. Thus, village funding and infrastructure development are key in improving the welfare of rural communities and reducing development gaps in the region.